Photoluminescence enhancement of CdSe quantum dots: A case of organogel-nanoparticle symbiosis - Wadhavane, Prashant D. (2012)
Highly fluorescent organogels (QD-organogel), prepared by combining a pseudopeptidic macrocycle and different types of CdSe quantum dots (QDs), have been characterized using a battery of optical and microscopic techniques. The results indicate that the presence of the QDs not only does not disrupt the supramolecular organization of the internal fibrillar network of the organogel to a significant extent, but it also decreases the critical concentration of gelator needed to form stable and thermoreversible organogels. Regarding the photophysical properties of the QDs, different trends were observed depending on the presence of a ZnS inorganic shell around the CdSe core. Thus, while the core-shell QDs preserve their photophysical properties in the organogel medium, a high to moderate increase of the fluorescence intensity (up to 528%) and the average lifetime (up to 1.7), respectively, was observed for the core QDs embedded in the organogel. The results are relevant for the development of luminescent organogels based on quantum dots, which have potential applications as advanced hybrid materials in different fields. © 2012 American Chemical Society.